2018
DOI: 10.3390/ijerph15091955
|View full text |Cite
|
Sign up to set email alerts
|

Mothers and Children Exposed to Intimate Partner Violence: A Review of Treatment Interventions

Abstract: Although a growing field, much is still unknown about how different clinical and social care services might improve outcomes for female victims of intimate partner violence (IPV) and their children who are indirectly exposed to it. This review sought to characterize the structure of programs that have been tested and documented in existing literature, and the mechanisms by which change, if any, may occur. Seventeen individual interventions and two follow-ups (n = 19) were included in the review. Findings sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 54 publications
2
53
0
1
Order By: Relevance
“…In this study, it was also found that the threat of leaving a relationship was one of the factors identified as being the reason for the perpetration of intimate partner violence on a partner. Previous studies (Abrahams, Jewkes, Hoffman, & Laubsher, 2004;Anderson & van Ee, 2018;Dichter & Gelles, 2012) have also made findings consistent with this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, it was also found that the threat of leaving a relationship was one of the factors identified as being the reason for the perpetration of intimate partner violence on a partner. Previous studies (Abrahams, Jewkes, Hoffman, & Laubsher, 2004;Anderson & van Ee, 2018;Dichter & Gelles, 2012) have also made findings consistent with this study.…”
Section: Discussionsupporting
confidence: 92%
“…However, in some situations, this is not done as found in this study. Some other literature has also supported this study (Anderson & van Ee, 2018;Rakovec-Felser, 2014). Again, some of the participants revealed that their partners instead of feeling remorseful rather argued with them which led to fights.…”
Section: Discussionsupporting
confidence: 81%
“…Multileveled programs of mothers and children working both separately and together across sessions might generate the most successful psychosocial recovery for mothers and children who have experienced violence in the home [69]. However, given the heterogeneity of existing interventions and the limitations of current research [70], it is not yet clear which interventions or intervention components are most effective in addressing the needs of women parenting in the context of IPV, so further research is needed.…”
Section: Conclusion and Proposals For Social Interventionmentioning
confidence: 99%
“…Providing earlier help and support for children and their families in response to emerging problems before they get worse is widely regarded as good safeguarding practice, but little is known about what forms of support are effective (Guy et al ., 2014). The Anderson and Ee (2018) review of 17 (mostly North American) interventions identified a paucity of early interventions focused specifically on children and mothers. This review emphasised that where interventions do exist, those that work with both mothers and their children in both separate and joint sessions are ‘believed to help sustain any positive changes within the family unit.…”
Section: Introductionmentioning
confidence: 99%